Emerging horizons on molecular and circulating biomarkers in pancreatic adenocarcinoma - Moretti, Marta; Farina, Antonella; Angeloni, Antonio; Anastasi, Emanuela (Frontiers in Oncology, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is the most aggressive and invasive type of pancreatic cancer and is expected to soon become the second leading cause of cancer-associated death. The high mortality rate is due to the clinical features that allow asymptomatic progression to advanced stages, a period when current therapeutic treatments have limited efficacy. To address these challenges, researchers are focused on identifying new molecular and circulating markers for early PDAC detection and precision medicine. In this mini-review, we report the most well-known and recently identified molecular and circulating biomarkers. This study aimed to emphasize the need for continued innovative research to develop diagnostic algorithms and therapies to improve the management of patients with PDAC.